Essential biology with physiology - Campbell, Neil A. (Pearson/​Benjamin Cummings, 2007)
The Second Edition features dynamic new resources designed to focus students’ study time and help them master the most challenging topics in the course. New state-of-the-art eTutor animations and audio MP3 Tutor Sessions guide students through the most challenging topics in biology. A customized Study Plan on the accompanying website pinpoints exactly where students have trouble, and directs them to relevant sections of the text and media for help.